Computer self-efficacy and computer anxiety: the effects on technology acceptance in implementing flipped learning approach - Abd Rahman, Siti Fatimah; Ahmad, Noorlila (RSIS International, 2025)
The technology acceptance model was initially constructed to explain the behavioural intention in adopting and utilising an information system. The model has been widely used to investigate the level of technological innovation adoption, particularly in computers and information systems. This study investigates the effects of computer self-efficacy and computer anxiety on the ESL lecturers’ technology acceptance adapting flipped learning approach. 206 Malaysian ESL public university lecturers participated in this study. Structural equation modelling (SEM) was used to analyse the data on the effects of computer self-efficacy and computer anxiety on ESL lecturers’ decisions about whether or not to integrate flipped learning in their teaching and learning. The findings show that Malaysian ESL lecturers are not stressed about handling new technology (software or hardware) and possess high computer self-efficacy. This result could help lecturers and stakeholders adapt and integrate flipped learning into teaching and learning